2002
DOI: 10.17221/4204-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different straw management practices on yields of continuous spring barely

Abstract: Field experiments were conducted in the maize-growing region on heavy gleic fluvisol from 1974 to 2000. Three variants of straw management (straw harvested, incorporated into soil and burned), two variants of soil tillage (conventional plough tillage to 0.22 m, shallow disc tillage to 0.12-0.15 m) and three variants of fertilization (30, 60 and 90 kg N.ha -1 ) were studied. After conventional tillage, the highest yield was obtained in the variant with burned straw (5.50 t.ha -1 ), followed by the variant with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Tyto výsledky korespondují se závěry Kose [1], který spatřuje příčinu ve zpomalování rozkladu slámy za horších vláhových podmínek a tím zesílení fytotoxického účinku. Z dosažených výsledků monokulturně pěstovaného ječmene jarního (1974 až 2000) na stanovišti v Žabčicích (kukuřičná výrobní oblast) poukázali Procházková et al [24] na vliv hloubky zapravované slámy do půdy na výnosy. V této souvislosti zaznamenali statisticky průkazný pokles výnosů zrna po mělkém a naopak nárůst výnosů po hlubším zapravování slámy.…”
Section: Období 2004--2006unclassified
See 1 more Smart Citation
“…Tyto výsledky korespondují se závěry Kose [1], který spatřuje příčinu ve zpomalování rozkladu slámy za horších vláhových podmínek a tím zesílení fytotoxického účinku. Z dosažených výsledků monokulturně pěstovaného ječmene jarního (1974 až 2000) na stanovišti v Žabčicích (kukuřičná výrobní oblast) poukázali Procházková et al [24] na vliv hloubky zapravované slámy do půdy na výnosy. V této souvislosti zaznamenali statisticky průkazný pokles výnosů zrna po mělkém a naopak nárůst výnosů po hlubším zapravování slámy.…”
Section: Období 2004--2006unclassified
“…He found the cause in slowing down straw degradation under adverse moisture conditions and thus in a stronger phytotoxic effect. The results of spring barley continuous cropping (1974-2000) on a site at Žabčice (maize growing region) obtained by Procházková et al [24] revealed the effect of the depth of straw incorporation into the soil on yields. They found statistically significant reductions in grain yields after shallow straw incorporation into the soil and yield increases after deeper straw incorporation.…”
mentioning
confidence: 98%
“…If there is no possibility for manure use, the plowing over the harvest residues is a good alternative that leads to the improved soil properties and high yields. The effect of plowing over harvest residues on the yield and quality of corn and grains was investigated worldwide and the country (Lemon-Ortega et al, 2000;Pracházková et al, 2002;Jaćimović et al, 2009;Latković et al, 2015;Jaćimović et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional rice cultivation in Thailand includes postharvest burning of rice straw residues to increase and sustain nutrients during the growing season. It has been demonstrated that this practice enhances rice yield components and as a result increases rice and barley yields (Procházková et al, 2002;Surekha et al, 2006).…”
Section: Introductionmentioning
confidence: 99%